The Relationship Between Vitamin D Levels in Pregnant Women and Spontaneous Abortion During Early Pregnancy - Alqani, Vian Hussam Almansi; Mohammed, Ashwaq Kadhim (Jurnal Kebidanan Midwiferia, 2025)
Background: About 10-15% of clinically detectable pregnancies end in a spontaneous abortion. This research set out to examine Iraqi pregnant women's vitamin D levels in connection to their risk of miscarriage. Our goal is to learn more about the correlation between vitamin D insufficiency and abortion rates by analyzing blood vitamin D concentrations in women who have experienced spontaneous miscarriages. Materials and methods: An investigation of a cross-sectional nature was carried out at the Al Diwaniya Maternity and Child Teaching Hospital in Iraq between the months of August 2016 and August 2017. Using well-established laboratory procedures, 42 women who had previously experienced an abortion of their own accord provided blood samples for the purpose of determining their vitamin D levels. Result: The average concentration of vitamin D in the serum was 21.48 ± 11.82 ng/ml, while sixty percent of the participants had levels that were insufficient (less than twenty ng/ml). It was shown that there was a significant negative correlation (r = -0.717, p < 0.001) between the levels of vitamin D and the occurrence of miscarriages. Using regression analysis, it was discovered that vitamin D levels were responsible for explaining 51.4% of the variance in the incidences of miscarriage. Conclusion: Vitamin D deficiency is significantly associated with an increased risk of spontaneous miscarriage. Preventing vitamin D insufficiency may reduce miscarriage rates among Iraqi women.